An Analysis Of Modal Ability Used in At My Worst Song - Azzahra, Safira; Amelia, Cindi; Rambe, Sutan Rizki (Jurnal Dieksis ID, 2024)
The song At My Worst by Pink Sweats carries a deep emotional message about interpersonal relationships, and one of the key elements in the song's lyrics is the use of modal verbs to convey emotional and interpersonal abilities. This study aims to analyze the use of modal verbs can, could, and be able to in the song, as well as to explore the meanings contained within them. The method used in this study is a descriptive qualitative approach, analyzing the song's lyrics as the subject of research. The instrument used is a text analysis to identify modal verbs that indicate ability, and data collection was carried out through documentation of the song's lyrics taken from accessible online sources. The results of the study show that the use of modal ability in this song does not only refer to physical abilities or skills, but also encompasses emotional abilities such as empathy, emotional management, and navigating loving relationships in imperfect conditions. Modal verbs can and could are frequently used to express hope and requests in interpersonal relationships, while be able to is less commonly used but still indicates potential or ability in an emotional context. This study contributes to the understanding of the role of modal ability in song lyrics and how these modal verbs are used to depict emotional dynamics and interpersonal relationships in contemporary music